ASSISTANCE IN DRAFTING COOPERATION AGREEMENTS FOR EMPLOYEES AND OTHER PARTNERS AT PT PUNDI SELARAS MAJU REGARDING LEGAL REFORMS IN INDONESIA - David Tan; Agus Susanto (ConCEPt - Conference on Community Engagement Project, 2022)
A company is formed to obtain a profit or profit so that in its implementation it is necessary to have a supporting factor, one of which is other partners / work partners and employees. Therefore, in its implementation, it is necessary to arrange an agreement that contains the regularity of the parties in carrying out their obligations and obtaining their rights so that the company can run well and develop. so that this practical work program is to prepare the company's legal documents.The problems found in the company include the existence of clauses that need to be regulated in the contents of the cooperation agreement with other partners previously so that it is necessary to renew the contents of the agreement in the cooperation contract and it is necessary to renew the contents of the employee contract cooperation agreement in accordance with applicable law in Indonesia.The implementation method used in the preparation is the empirical method which is carried out by observing, interviewing and collecting the necessary literature study data, and the result of the preparation of the practical work program is to obtain a cooperation agreement with other partners and employees that has been renewed.